2020
DOI: 10.1103/physreva.101.023604
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-induced entanglement in a mass-imbalanced few-fermion system

Abstract: Many-body systems undergoing quantum phase transitions reveal substantial growth of non-classical correlations between different parties of the system. This behavior is manifested by characteristic divergences of the von Neumann entropy. Here we show, that very similar features may be observed in one-dimensional systems of a few strongly interacting atoms when the structural transitions between different spatial orderings are driven by a varying shape of an external potential. When the appropriate adaptation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Contrary, in the harmonic potential (λ = 1), the lighter component is split and located on the edges while the heavier one remains in the center. Following this observation, it was shown that the system undergoes some sort of critical transition when one adiabatically changes parameter λ from 0 to 1 [17,18]. It turned out that the transition has properties quite similar to that known from typical quantum phase transition, e.g.…”
Section: The System Studiedmentioning
confidence: 67%
See 4 more Smart Citations
“…Contrary, in the harmonic potential (λ = 1), the lighter component is split and located on the edges while the heavier one remains in the center. Following this observation, it was shown that the system undergoes some sort of critical transition when one adiabatically changes parameter λ from 0 to 1 [17,18]. It turned out that the transition has properties quite similar to that known from typical quantum phase transition, e.g.…”
Section: The System Studiedmentioning
confidence: 67%
“…It means that a role of the thermodynamic limit is played by a limit of infinite repulsions [17]. The analogy to typical quantum phase transitions was supported further in [18] by confirming that quantum correlations between different parties of the system, quantified by appropriate entanglement entropies, are also power-law divergent in the transition point [19][20][21].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations